Strengthening credit rating integrity. Issue 4 (9th November 2015) - Adelson, Mark; Jacob, David
Abstract : Purpose: – The purpose of the article is to explain the significance of key features of the SEC's new rules for credit rating agencies. Those rules include three key items: they prohibit the influence of sales or marketing considerations on criteria development; they include guidance that preserves the ability of ratings to serve as relative rather than absolute measures of credit risk; and they require cross-sector consistency of rating symbols. When they were released the significance of the rules was under-appreciated because of other simultaneous regulatory announcements. Design/methodology/approach: – The approach is to consider how effectively the rules address their target issues. In doing so the article explores how the final rules evolved from their original proposed form and from the statutory specifications in the 2010 Dodd-Frank Act. Findings: – The new rules should promote the integrity of credit ratings in the future. They should be effective in reducing the influence of sales and marketing considerations on the development of rating criteria. In addition they should enhance rating integrity through superior cross-sector consistency in the meanings of rating symbols while allowing rating agencies to maintain their traditional emphasis on relative risk. Originality/value: – The authors are not aware of any similar work assessing the selected provisions of the new SEC rules for credit rating agencies.